Low-Intensity Resistance Exercise Combined With Blood Flow Restriction is More Conducive to Regulate Blood Pressure and Autonomic Nervous System in Hypertension Patients—Compared With High-Intensity and Low-Intensity Resistance Exercise - Zhao, Yan; Zheng, Yuchan; Ma, Xiaohuan; Qiang, Lili; Lin, Aicui; Zhou, Mo (Frontiers in Physiology, 2022)
Background: The effect of resistance exercise on the autonomic nervous system of patients with hypertension has not been identified. Objective: To explore a suitable resistance training method for hypertension patients to regulate blood pressure (BP) and autonomic nervous system function. Method: Forty-five hypertension patients aged between 55 to 70 years were randomly equally divided into 3 groups: the high-intensity resistance exercise (HE) group, the low-intensity resistance exercise combined with blood flow restriction (LE-BFR) group, and the low-intensity resistance exercise (LE) group. All patients performed quadriceps femoris resistance exercise. The exercise intensity of HE, LE-BFR and LE group was 65%, 30% and 30% of one repetition maximum (1RM), respectively. The LE-BFR group used pressure cuffs to provide 130% of systolic pressure to the patient’s thighs during resistance exercise. The training program was 20 times/min/set with a 1-min break after each set, and was conducted five sets/day and 3 days/week, lasting for 12 weeks. The heart rate (HR), BP, root-mean-square of difference-value of adjacent RR intervals (RMSSD), low frequency (LF) and high frequency (HF) were evaluated before and after the first training and the last training. Result: Significant differences in HR were observed in both recovery states after the first and last training (P<0.01). After 12 weeks of training, the recovery speed of HR in the LE-BFR group increased significantly (P<0.01). The systolic blood pressures in the HE and LE-BFR group were significantly reduced (P<0.05 & P<0.01), and the differences among groups were significant (P<0.01). In the last recovery state, the RMSSD of the LE group was significantly lower than that in the first recovery state (P<0.01). The LF/HF ratios of the HE and LE groups in the resting and recovery states were increased significantly (all P<0.01). LF/HF ratios in the LE-BFR group in the resting and recovery state were decreased significantly (both P<0.01). Conclusion: Compared to HE and LE, LE-BFR could effectively decrease systolic pressure and regulate the autonomic nervous system function in hypertension patients.